Analysis of the Effect of Direct Payments from the Owner to Nominated Subcontractors on Project Sustainability - A. F, M. Dhika Adhitya; Hardjomuljadi, Sarwono (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the construction industry, the practice of direct payments by service users to subcontractors has become a common phenomenon. This practice occurs when service users, as main clients, pay subcontractors directly without going through the main contractor. This aims to speed up cash flow and ensure timely payments to subcontractors. However, the practice of direct payments also raises various problems and impacts that need to be considered. In this research, the approach used is quantitative. This research uses a causal analysis method because this research aims to test a hypothesis regarding the influence of one or several independent variables on the dependent variable. The population determined in this research includes building project stakeholders who focus on: Project Owners, and Main Contractors, Sub-contractors / Suppliers, totaling 110 respondents, using the Slovin formula with a 5% margin of error, the number of respondents was 86 people. Payment research results in direct project payments have a positive and significant effect on project costs, direct project payments have a positive and significant effect on project time, and direct project payments have a positive and significant effect on project quality.